Oral Performance, Literary Authority, and Vernacular Transposition: The Shreemad Bhagavat Saptaha Tradition in the Indian and Nepalese Narrative Canon - Neupane, Dasarath; Mariam, Alesh (NPRC Journal of Multidisciplinary Research, 2026)
Introduction: The Shreemad Bhagavat Saptaha is an important ongoing tradition in Hindu practices that still needs to be explored extensively in literary and performance studies. The issues regarding the role of oral performance, literary text, and vernacular literature in the tradition provide essential insights into ways in which religious texts create meaning through performances beyond the written word. Research Objectives: The research examines three interrelated aspects: (1) the dynamic between the oral and textual authority in the Saptaha tradition, (2) the implications of traditional aesthetics (rasa) for creation and performance of the Bhagavatam, and (3) the contribution of the Saptaha tradition to Indian vernacular literature. Methods: The study combines text analysis of the Sanskrit Bhagavatam (Books 1, 10, and 11) with ethnography of Saptaha performances through published works on the topic (Taylor 2012a, 2012b), complemented by comparative text analysis of vernacular translations of Bhagavatam into Hindi, Bengali, Nepalese, and Telegu languages. Analysis: Results show that Saptaha is a "performative literary event" where Sanskrit is used as a means of ritual empowerment and vernacular texts hold narrative value, that the Bhagavatam uses Bharata’s rasa classification system with shringara being its most important category, and that the vernacular texts have been granted their own scriptural authority. Conclusion: Through Saptaha, the western paradigm of textuality faces challenge due to embodiment. Digital Saptahas and other oral traditions need further analysis.